Mechanical Cues Affect Migration and Invasion of Cells From Three Different Directions - Mierke, Claudia Tanja (Frontiers in Cell and Developmental Biology, 2020)
Cell migration and invasion is a key driving factor for providing essential cellular functions under physiological conditions or the malignant progression of tumors following downwards the metastatic cascade. Although there has been plentiful of molecules identified to support migration and invasion of cells, mechanical aspects have not yet been explored in a combined and systematic manner. In addition, cellular environment has been classically and frequently assumed to be homogeneous for reasons of simplicity. However, motility assays have led to various models for migration covering only some aspects and supporting factors that in some cases include mechanical factors. Instead of specific models, in this review, a more or less holistic model for cell motility in 3D is envisioned covering all these different aspects with a special emphasis on mechanical cues from a biophysical perspective. After introducing mechanical aspects of cell migration and invasion and presenting heterogeneity of extracellular matrices, the three distinct directions of cell motility focusing on mechanical aspects are presented. These three different directions are: firstly, commonly used invasion tests using structural and structure-based mechanical environmental signals; secondly, mechano-invasion assay, in which cells are studied by mechanical forces to migrate and invade; and thirdly, cell mechanics, including cytoskeletal and nuclear mechanics, to influence cell migration and invasion. Since the interaction between the cell and the microenvironment is bi-directional in these assays, these should be accounted in migration and invasion approaches focusing on mechanical aspects. Beyond this, there is also the interaction between the cell's cytoskeleton and its other compartments, such as cell nucleus. In specific, a three-element approach is presented for addressing the effect of mechanics on cell migration and invasion by including the effect of the mechano-phenotype of the cytoskeleton, nucleus and cell’s microenvironment into the analysis. In precise terms, combination of these three research approaches including experimental techniques seems to be promising for revealing bi-directional impacts of mechanical alterations of cellular microenvironment on cells and internal mechanical fluctuations or changes of cells on the surroundings. Finally, different approaches are discussed and thereby a model for the broad impact of mechanics on cell migration and invasion is evolved.